It goes on: Oil Palm Plantations, Local Communities and Land Conflict in West Pasaman District, Indonesia - Edi Indrizal; Ermayanti; Ade Irwandi; Hairul Anwar; Rizka Ananda Alyan (Direktorat Riset dan Pengabdian Kepada Masyarakat, 2024)
This research seeks to elucidate the conflict over PT PHP I's CultivationRights Title (HGU), claimed as customary land by some communities inNagari Kapa. It aims to detail the customary elements that legitimized the1997 land rights transfer to the West Pasaman Regency government. Theissue stems from internal conflicts among Nagari Kapa's customary elites,impacting PT PHP I as the HGU holder. The disputed area encompasses 315hectares of PT PHP I's land, occupied by the community since 2020. Usingethnographic methods, the study explores community and tribal leaders'(Ninik Mamak) perspectives on customs and land status. Interviews wereconducted with 10 groups of tenant farmers on PT PHP I's core HGU landand 5 Ninik Mamak. Findings reveal that land status, under the BabingkahAdat system, is determined by the Pucuk Adat and transferred according toAdat Diisi Limbago Dituang and Siliah Jariah customary requirements.However, some community members oppose this mechanism, occupying landdesignated as PT PHP I's HGU, and thus, they collectively claim the land ascustomary territory of the Nagari Kapa community.